PENDIDIKAN KARAKTER BERBASIS NILAI-NILAI AGAMA DAN MORAL DI RAUDHATUL ATFAL AL-ISHLAH KOTA GORONTALO - Samsi Pomalingo; Wirna Tangahu (Bajang Institute, 2022)
Character education is an effort made to guide and direct someone to behave well in life. The values of character education taught include faith, caring, honesty, discipline, cleanliness, respect and courtesy. The development of student character at Raudhatul Atfal Al-Ishlah does not only from the curriculum that has been prepared by the institution, but also uses the Koran and the Hadith of the Prophet as a source in the application of character education for students. No wonder this school is named as the center for integrated Islamic Early Childhood Education (PPIT) al-Ishlah. Because it makes the Koran and Hadith as a source of reference or references in inculcating religious and moral-based character values for students. But on the other hand the role model (figure), the lack of discipline from some teachers and the habituation of good character in children at school are not continued by parents when the children are at home, and ta'lim activities for parents are less than optimal become obstacles in sustainability of character education. This study focuses on how to implement character education based on religious and moral values in Raudhatul Atfal al-Islah, Gorontalo City. This research model is a qualitative research. Data collection techniques were carried out through participatory observation, interviews, and documentation.